2021
DOI: 10.3390/mi12091123
|View full text |Cite
|
Sign up to set email alerts
|

Process Optimization of Silver Nanoparticle Synthesis and Its Application in Mercury Detection

Abstract: Silver nanoparticles (AgNPs) have stable reactivity and excellent optical absorption properties. They can be applied in various industries, such as environmental protection, biochemical engineering, and analyte monitoring. However, synthesizing AgNPs and determining their appropriate dosage as a coloring substance are difficult tasks. In this study, to optimize the process of AgNP synthesis and obtain a simple detection method for trace mercury in the environment, we evaluate several factors—including the reag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…The formation of AgNPs is related to the reaction conditions. The procedure for this experiment can be found in our previous report [ 41 ]. The measured particle size was in the range of 20–110 nm, and the size with the highest frequency was approximately 47 nm, similar to the results obtained using a nanoparticle size analyzer [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of AgNPs is related to the reaction conditions. The procedure for this experiment can be found in our previous report [ 41 ]. The measured particle size was in the range of 20–110 nm, and the size with the highest frequency was approximately 47 nm, similar to the results obtained using a nanoparticle size analyzer [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research reported that linearity is the evaluation criterion for the best volume ratio, and 400 nm absorbance is used as the observation condition. The best volume ratio of reagents is 1:0.5, in order to achieve a linearity of at least R2 > 0.99 [ 41 ]. As the standard concentration of mercury increases, the color produced by the reaction between AgNPs and mercury gradually changes from yellow to light yellow and finally becomes transparent through the adsorption of mercury ions into AgNPs to form amalgam crystals [ 45 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation reaction of silver nanoparticles was compared with the use of hot water and an ice bath. When using hot water, the characteristic of the color and absorption is better than in cold water [55].…”
Section: Temperaturementioning
confidence: 99%
“…Fu et al [55], that use silver nanoparticles as a colorimetric sensor for mercury detection in the environment, also evaluated several factors optimization on the formation of AgNPs, including reaction temperature. The formation reaction of silver nanoparticles was compared with the use of hot water and an ice bath.…”
Section: Temperaturementioning
confidence: 99%